Evaluasi Aksesibilitas Sarana dan Prasarana di Universitas Sebelas Maret melalui Pemetaan Spasial - Ummul Mustaqimah; Munawir Yusuf; Joko Yuwono; Mahardika Supratiwi; Redydian Adhitya Nugraha (Universitas Sebelas Maret Surakarta, 2024)
Universitas Sebelas Maret is committed to strengthening its inclusive identity by providing accessible facilities and infrastructure for people with disabilities. This research evaluates existing conditions and their conformity with building regulations. The goal is to provide information on accessible facilities and infrastructure, as well as to offer recommendations for improving them based on the principles of ease, safety, and comfort for people with disabilities within the UNS campus. The mapping was conducted through field surveys across all campus buildings, covering attributes such as ramps, pedestrian pathways, guide paths, toilets, elevators, and designated parking, in accordance with PUPR No. 14 of 2017. The results show that many facilities and infrastructure do not meet the required physical standards, indicating a need for better future planning to optimize accessibility.